DATA PRIVACY POLICY IN THE DIGITAL AGE: IMPLICATIONS, IMPLEMENTATION, AND IMPACT ON USERS - Gunawan Widjaja (Adisam Publisher, 2025)
The development of digital technology has brought significant changes in the management of personal information, making data privacy policies a crucial issue in the modern era. This study aims to analyse the implications, implementation, and impact of data privacy policies on users, emphasising the global and national contexts, particularly after the enactment of the Personal Data Protection Law (PDP Law) in Indonesia. The research approach used is descriptive qualitative with literature analysis. The results show that data privacy policies have broad implications, including strengthening fundamental individual rights, increasing corporate transparency, and creating new data security standards. However, their implementation faces challenges in the form of low digital literacy among the public, high compliance costs for companies, and potential user resistance to the complexity of the policies. The impact on users is twofold: on the one hand, it provides legal protection and a sense of security, but on the other hand, it creates a dilemma regarding ease of use and limited access to services. Therefore, the success of privacy policies requires synergy between adaptive regulations, digital corporate compliance, and increased digital literacy among the public in order to create a digital ecosystem that is secure, transparent, and fair.